2014
DOI: 10.1093/jis/14.1.123
|View full text |Cite
|
Sign up to set email alerts
|

Seasonality in the dung beetle community in a Brazilian tropical dry forest: Do small changes make a difference?

Abstract: Dung beetle (Coleoptera: Scarabaeoidea: Scarabaeinae) activity is influenced by rainfall seasonality. We hypothesized that rainfall might also play a major role in regulating the community structure of this group. In this study, we describe seasonal changes in the richness, composition, and structure of the Scarabaeinae community in a Brazilian tropical dry forest. A fragment of arboreal Caatinga was sampled using baited pitfall traps during the early dry season (EDS), late dry season (LDS), early wet season (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Seasonality did not significantly influence the carabid beetle assemblage, even though numerous studies have shown seasonality to be important in dry forest beetles (e.g., Novais et al 2016 ; Pérez and Zaragoza 2016; Rangel-Acosta and Martínez-Hernández 2017 ; Noguera et al 2018 ). However, there are exceptions; for example dung beetle richness differences between wet and dry seasons in the Caatinga forest in Brazil were small ( Medina and Lopes 2014 ). A reason for the lack of a seasonality signal in our data may, again, be due to a deficit in precipitation during the 2015/6 El Niño southern oscillation.…”
Section: Discussionmentioning
confidence: 99%
“…Seasonality did not significantly influence the carabid beetle assemblage, even though numerous studies have shown seasonality to be important in dry forest beetles (e.g., Novais et al 2016 ; Pérez and Zaragoza 2016; Rangel-Acosta and Martínez-Hernández 2017 ; Noguera et al 2018 ). However, there are exceptions; for example dung beetle richness differences between wet and dry seasons in the Caatinga forest in Brazil were small ( Medina and Lopes 2014 ). A reason for the lack of a seasonality signal in our data may, again, be due to a deficit in precipitation during the 2015/6 El Niño southern oscillation.…”
Section: Discussionmentioning
confidence: 99%
“…Also, there are few studies on dung beetle fauna in TDFs in South America (Neves et al . 2010; Medina & Lopes 2014; Novais et al . 2016; Vieira et al .…”
Section: Introductionmentioning
confidence: 99%
“…These variables are important drivers of biological diversity during and after the LGM (Collevatti et al 2013;Arruda et al 2018). Also, there are few studies on dung beetle fauna in TDFs in South America (Neves et al 2010;Medina & Lopes 2014;Novais et al 2016;Vieira et al 2017), being most studies spatially limited. Therefore, there is a need to evaluate the dung beetle patterns across the TDFs distribution aiming to contribute to the ongoing debate on TDFs origin.…”
Section: Introductionmentioning
confidence: 99%
“…Seasonality did not significantly influence the carabid beetle assemblage, even though numerous studies have shown seasonality to be important in dry forest beetles (e.g., Noguera et al 2018;. However, there are exceptions; for example dung beetle richness differences between wet and dry seasons in the Caatinga forest in Brazil were small (Medina & Lopes, 2014). A reason for the lack of a seasonality signal in our data may, again, be due to a deficit in precipitation during the 2015/6 El Niño southern oscillation.…”
Section: Discussionmentioning
confidence: 80%
“…Cerambycidae (Noguera-Martínez et al 2007;Noguera et al 2018;Noguera et al 2002;Toledo et al 2002), Scarabaeidae (Liberal et al 2011; and Staphylinidae (Jiménez-Sánchez et al 2009), but not for dung beetle richness in Brazil (Medina & Lopes, 2014), since differences between the wet and dry season are small. Insect seasonal patterns are affected by the relationship among community variables and rainfall (Jiménez-Sánchez et al 2009;Liberal et al 2011; or air humidity (García et al 2001;, demonstrating the important role of water for these organisms.…”
Section: Tdf Insects: Dynamics and Successionmentioning
confidence: 99%